2021
DOI: 10.1097/md.0000000000026768
|View full text |Cite
|
Sign up to set email alerts
|

Pain control and related factors in hospitalized patients

Abstract: Pain is a common health problem for hospitalized patients. It is necessary to understand the factors that affect patients’ pain to provide individual and complete pain management. This study explored the severity and incidence of pain in hospitalized patients on the admission day, during the hospitalization, and the discharge day, and explored the predictive factors that affect the patient's pain on the discharge day.This was a retrospective study that reviewed the medical records of 73,814 hospitalized patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
(68 reference statements)
0
8
0
1
Order By: Relevance
“…Pain can even last more than 3 months and become a chronic pain that can affect the patient’s quality of life, work and sleep. It also causes patients to seek medical care repeatedly, which indirectly leads to increased costs on the Healthcare system (Lin et al, 2021). Therefore, the provision of proper pain management for inpatients is an important issue that cannot be ignored.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain can even last more than 3 months and become a chronic pain that can affect the patient’s quality of life, work and sleep. It also causes patients to seek medical care repeatedly, which indirectly leads to increased costs on the Healthcare system (Lin et al, 2021). Therefore, the provision of proper pain management for inpatients is an important issue that cannot be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…While in the hospital, the level of pain on the day of admission, the emotional stress on the day of admission, and the emotional distress on the day of returning home were significantly correlated positively with the level of pain. The longer the patients stay in the hospital, the higher the level of pain on the day of admission, the greater the emotional stress on the day of admission and the greater the emotional stress on the day of exit (Lin et al, 2021).…”
Section: Ontological Studies On Painmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors include but are not limited to the patient gender, age, length of hospital stay in addition to the familial, psychological, social and cultural variables. [66,67]…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, non-conformity to guidelines in POP management can generate clinical and psychological adverse events 6 . It has been reported that 29 % of hospitalized patients experienced moderate to severe pain during rest and 41 % during activity 13 . The lack of proper pain management may lead to the persistence of the pain after discharge 7 .…”
Section: Introductionmentioning
confidence: 99%